Sistem Informasi Monitoring Absensi Menggunakan Framework COBIT 4.1 - Cipta M Pasaribu; Mega Mustika; Dewi Rosmayanti; Abdul Rahman Kadafi; Eko Setia Budi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Aprogress in every field cannot be separated from technology as a support, especially IT, it must be balanced with an evaluation or audit of information systems so that losses can be prevented or avoided. Therefore, the company needs to carry out a control and audit of the information system at the company. Control techniques can be applied and aligned with IT goals and company goals, a measurement of the level of alignment between company goals and IT goals is needed using COBIT4.1. COBIT 4.1 is specific to the Monitoring and Evaluation (ME) domain.